(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The history of the development of international civil aviation has marked a qualitative leap in the evolution of transport systems, becoming an integral part of the processes of globalization. Having started its journey in the first decades of the last century, by the 1950s it had acquired the status of a key industry that had a significant impact on the economic potential of countries and radically changed the system of global transport communications. Nowadays, the air transport industry is in a state of constant improvement, responding promptly to changing global market conditions and implementing advanced technical solutions. This process is particularly relevant for the intercontinental states, including Kyrgyzstan, where the development of the air transport system has a particular strategic importance. In this regard, special emphasis is placed on the consideration of such aspects as: the development of the civil aviation industry in Kyrgyzstan, the implementation of transport policy in the EAEU, integration measures in the field of civil aviation, the development of aviation infrastructure facilities in Kyrgyzstan, the activities of domestic airlines and their development prospects. The purpose of the study is to analyze the current state and prospects for the development of civil aviation in Kyrgyzstan in the context of integration into the Eurasian Economic Union (EAEU), as well as identify key problems and possible solutions. The scientific significance of the work lies in the comprehensive study of problematic issues of the industry, taking into account the development of Eurasian integration. Practical recommendations are offered to improve the competitiveness of the industry in Kyrgyzstan. The successful development of Kyrgyzstan’s civil aviation requires coordinated actions at the national and supranational levels, including adaptation to the EAEU common markets and technological modernization. The article offers a list of measures for the sustainable growth of the industry, which may be useful for government agencies (industry regulators), aviation experts and the scientific community.